"Historical Consciousness of the Youth of Uzbekistan in the Era of Digital Communications: New Forms of Perceiving the Past" - Akhmadjonova Munisa (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The digital transformation of the socio-cultural environment in Uzbekistan has led to a reconfiguration of the mechanisms through which young people engage with the historical past. This article explores the dynamics of historical consciousness formation among Uzbek youth in the era of digital communications, considering digital media not only as a technological tool but as a culturally significant space for memory production. The research analyzes how online platforms, social media, and state-supported digital heritage initiatives influence the interpretation, emotional appropriation, and personalization of historical narratives. The study identifies both integrative effects—such as increased accessibility to historical content and the emergence of participatory forms of memory—and potential risks associated with fragmentation, mythologization, and algorithm-driven selectivity of historical information.